2009
DOI: 10.1002/jhet.181
|View full text |Cite
|
Sign up to set email alerts
|

About the reaction of β‐dimethylamino‐α,β‐enones with active methylene nitriles

Abstract: magnified imageThe reaction of 3‐dimethylamino‐1‐arylpropenone derivatives with active methylene nitriles was reinvestigated and a plausible mechanism to account for the results is suggested. X‐ray crystallographic study supported the suggested mechanism. Based on these findings, the reaction of 3‐acetylamino‐4‐dimethylaminobut‐3‐en‐2‐one with malononitrile was also reinvestigated and the correct structures verified. J. Heterocyclic Chem., (2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
5
16
0
Order By: Relevance
“…Although it was proposed earlier that these products are conjugated amino nitriles, A, [12], we recently established on the basis of both Xray and 15 N NMR analysis that the products actually are the enedienes 12a,b (Scheme 2). Recently Abdelrazik [13] and Gorobets [14] have reached the same conclusion based on Xray crystallographic analysis results. Further support of the newly assigned structures comes from the observation that enediene12c undergoes cyclization to give 14 when stirred in refluxing glacial acetic acid.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Although it was proposed earlier that these products are conjugated amino nitriles, A, [12], we recently established on the basis of both Xray and 15 N NMR analysis that the products actually are the enedienes 12a,b (Scheme 2). Recently Abdelrazik [13] and Gorobets [14] have reached the same conclusion based on Xray crystallographic analysis results. Further support of the newly assigned structures comes from the observation that enediene12c undergoes cyclization to give 14 when stirred in refluxing glacial acetic acid.…”
Section: Resultssupporting
confidence: 56%
“…However, the acyclic substance 23 could be readily ruled out on the basis of both IR and 13 C NMR spectroscopic properties, which ruled out the presence of a cyano group in the products. However, in spite of reports to the contrary, [13] pyraneimines like 24 are highly unstable substances. This consideration led us to propose that the products of these reactions have the pyridone structures 25a,b.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Due to their biological activities and pharmacological properties, pyridines and pyridones represent an important class of compounds that have been developed using functionally substituted enaminones [16][17][18][19][20][21][22]. In continuation of our interest in the synthesis of functionally substituted heteroaromatic compounds such as pyridines and pyridones, utilizing enaminones as starting materials [22][23][24][25][26][27][28][29][30][31][32][33], we report here the behavior of 3-anilinoenone and N-phenyl cinnamamide derivative toward malononitrile in the synthesis of pyridine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Abdelrazek and Elsayed [20] have reported that the reaction of enaminones 1a-b with active methylene nitriles afforded pyridone 8 through the isolated intermediate 7. The authors proposed a synthetic pathway for the formation of 2-pyridone 8 includes 1,4-addition of active methylene in malononitrile to dimethylamino group of enaminone 1 rather than 1,2-addition to the carbonyl group (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%